Association of plain computed tomography‐determined pulmonary artery‐to‐aorta ratio with clinical severity of coronavirus disease 2019. (1st November 2020) - Hayama, Hiromasa; Ishikane, Masahiro; Sato, Rubuna; Kanda, Kohei; Kinoshita, Noriko; Izumi, Shinyu; Ohmagari, Norio; Hiroi, Yukio
Abstract : Coronavirus disease (COVID‐19) is associated with pulmonary hypertension due to pulmonary embolism, which affects subsequent outcomes. However, definitive diagnosis of pulmonary hypertension is difficult because of the risk of spreading the infection. Here, we assess the utility of plane computed tomography in noninvasively predicting the clinical severity of COVID‐19.